1981
DOI: 10.1128/aac.19.5.740
|View full text |Cite
|
Sign up to set email alerts
|

Moxalactam therapy for a wide spectrum of bacterial infections in adults

Abstract: We evaluated the efficacy and toxicity of moxalactam during treatment of 45 documented infections in 36 patients. A majority of patients received 4.5 g of moxalactam per day. There was a good clinical response in 42 of the 45 (94%) infections, including 3 bacteremias, 20 skin and soft tissue infections, 6 gramnegative lower respiratory tract infections, 6 purulent diabetic foot ulcers, 3 wound infections, 3 urinary tract infections, and 4 miscellaneous infections (meningitis, suppurative phlebitis, peritonitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Except for nonfermentative organisms, its activity against aerobic gram-negative bacilli is equal to or exceeds that of currently available aminoglycosides and other beta-lactams (1,6). Moxalactam has been shown to be effective in infections caused by susceptible bacteria (14,15). Its toxicity has been minimal and similar to that of previous cephalosporins.…”
mentioning
confidence: 86%
“…Except for nonfermentative organisms, its activity against aerobic gram-negative bacilli is equal to or exceeds that of currently available aminoglycosides and other beta-lactams (1,6). Moxalactam has been shown to be effective in infections caused by susceptible bacteria (14,15). Its toxicity has been minimal and similar to that of previous cephalosporins.…”
mentioning
confidence: 86%
“…Eosinophilia, elevated liver function tests, and thrombocytosis have been previously associated with the administration of third-generation cephalosporins. Eosinophilia has been reported in 4 to 11% of patients receiving moxalactam (13,27) (13,27). Though thrombocytosis can be associated with the stress of infection, a clear temporal relationship between the onset of thrombocytosis and the initiation of ceftriaxone therapy was apparent in these cases.…”
Section: Methodsmentioning
confidence: 96%
“…Though thrombocytosis can be associated with the stress of infection, a clear temporal relationship between the onset of thrombocytosis and the initiation of ceftriaxone therapy was apparent in these cases. Thrombocytosis has also been reported in 7 of 36 patients (19%) receiving moxalactam (27).…”
Section: Methodsmentioning
confidence: 97%
“…For at least 4 h after the dose, mean serum levels were more than twice the maximum MIC for susceptible bacteria (5 ,ug/ml). Previous studies with adults (5,6,10) showed that moxalactam had a relatively small incidence of serious adverse effects. In our study, five patients developed neutropenia which resolved after therapy was completed.…”
mentioning
confidence: 99%
“…Recent clinical trials (5,6,10) in adult patients have shown that a variety of acute bacterial infections are successfully treated with moxalactam. A low incidence of drug-associated adverse reactions was reported in these studies.…”
mentioning
confidence: 99%